1986
DOI: 10.1002/arch.940030709
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of sequential larval cuticular gene expression

Abstract: As the tobacco hornworm (Manduca sexta) larva feeds and grows, the abdominal epidermis synthesizes larval endocuticular proteins. During a molt this synthesis temporarily ceases while the cells deposit a new epicuticle; then these proteins reappear in a sequential manner, some before ecdysis, others after ecdysis. At the time of metamorphosis, the epidermis becomes pupally committed and ceases synthesizing these endocuticular proteins. Northern and dot blot hybridization analysis using cDNA clones for three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…the fall of the pupal ecdysteroid titre (Delbecque et a/., 1978). This time correlation is in agreement with previous experiments on Drosophila Doctor et a/., 1985; Fristrom 8, Liebrich, 1986) and on Manduca (Riddiford, 1986), which show that cuticular secretion needs a decrease in the ecdysteroid titre following an initial pulse. Recently, Apple & Fristrom (1991), using nuclear run-on experiments with Drosophila EDG cuticular genes, demonstrated that this regulation was at the transcriptional level.…”
Section: Cagttgttcaacatcgatcaaagcaataacaacaacaagaacat(iagattatttattsupporting
confidence: 91%
“…the fall of the pupal ecdysteroid titre (Delbecque et a/., 1978). This time correlation is in agreement with previous experiments on Drosophila Doctor et a/., 1985; Fristrom 8, Liebrich, 1986) and on Manduca (Riddiford, 1986), which show that cuticular secretion needs a decrease in the ecdysteroid titre following an initial pulse. Recently, Apple & Fristrom (1991), using nuclear run-on experiments with Drosophila EDG cuticular genes, demonstrated that this regulation was at the transcriptional level.…”
Section: Cagttgttcaacatcgatcaaagcaataacaacaacaagaacat(iagattatttattsupporting
confidence: 91%
“…4,5 JH has profound influence on the insect life cycle by hindering larva metamorphosis and by regulating embryogenesis, stimulating reproductive maturation, and controlling the metabolism and migratory behavior of adults. [6][7][8] In insect hemolymph, three separate groups 2,9,10 of high-affinity proteins bind JH, namely, the most abundant high molecular weight lipophorins with up to 50% lipid content, the hexameric high molecular weight proteins with 15% lipid content, and the low molecular weight (LMW; molecular weight 25,000-30,000) proteins so far detected in Lepidopetra and Diptera. The third group is of special interest as these proteins bind 99% of JH in the hemolymph despite their low abundance-below 1% of total protein content.…”
Section: Introductionmentioning
confidence: 99%
“…This paper represents a dovetail of our interests in iron metabolism and hormonal control of gene expression in insects. It originated with isolation of an anonymous cDNA to a cockroach (Blaberus discoidalis) fat body mRNA that was, in the adult female, markedly suppressed by the sesquiterpenoid juvenile hormone (H), a principal regulator of insect development and reproduction (22,23). DNA sequence analysis indicated that the JH-regulated cockroach message codes for a protein homologous to the vertebrate transferrins and transferrin from M. sexta, a distantly related insect.…”
mentioning
confidence: 99%